Akibat Hukum Bagi Perseroan Terbatas Yang Memberi Upah Kepada Pekerjanya Dibawah Ketentuan Upah Minimum Ditinjau Dari Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja (Studi Kasus PT. Lapisan Seribu Warna Cabang Surabaya) - Achmad Arney Iskandar; Anajeng Esri Edhi (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2023)
This study aims to analyze the legal consequences that may be faced by a Limited Liability Company (Ltd) that pays its workers below the minimum wage, using Law Number 11 of 2020 “Cipta Kerja” as its legal basis. The case study used is PT. Lapisan Seribu Warna Surabaya Branch. The method used in this research is normative juridical, with reference to laws and regulations related to the minimum wage and the provisions contained in Law Number 11 of 2020 “Cipta Kerja”. The results of the research show that PT. Lapisan Seribu Warna Surabaya Branch has violated the minimum wage provisions stipulated in the law. The legal consequences that may be faced by company may be subject to administrative sanctions in the form of fines by the local “Badan Pengawas Ketenagakerjaan (BPTK)”